2022
DOI: 10.1530/eje-21-0625
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced performance of a modified diagnostic test of primary aldosteronism in patients with adrenal adenomas

Abstract: Objective: Primary aldosteronism (PA) is the commonest cause of endocrine hypertension ranging from 4.6%-16.6% according to the diagnostic tests employed. The aim of this study was to compare the traditional saline infusion test (SIT) with the modified post-dexamethasone SIT (DSIT) by applying both tests on the same subjects. Methods: We studied 68 patients (72% hypertensives) with single adrenal adenoma and 55 normotensive controls, with normal adrenal imaging. Serum cortisol, aldosterone and plasma renin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Piaditis et al reported a 24.1% prevalence of 'subtle AAS' among patients with a single adrenal adenoma in a case-control study, in which Ald and DRC cutoffs were established for a DXM-enhanced saline infusion test based on data obtained from controls with NT and normal adrenal glands [16]. A similar (29.4%) biochemically overt PA prevalence was obtained with the same approach by these researchers recently, and, crucially, MRA and adrenalectomy were highly effective in the therapy of HT among PA patients [17]. While our approach of using merely a permissive ADRR to diagnose AAS is perhaps overly simplistic, an assessment of the congruity between these would be valuable (the mean basal ADRR of adrenal adenoma patients was ca.…”
Section: Discussionmentioning
confidence: 67%
“…Piaditis et al reported a 24.1% prevalence of 'subtle AAS' among patients with a single adrenal adenoma in a case-control study, in which Ald and DRC cutoffs were established for a DXM-enhanced saline infusion test based on data obtained from controls with NT and normal adrenal glands [16]. A similar (29.4%) biochemically overt PA prevalence was obtained with the same approach by these researchers recently, and, crucially, MRA and adrenalectomy were highly effective in the therapy of HT among PA patients [17]. While our approach of using merely a permissive ADRR to diagnose AAS is perhaps overly simplistic, an assessment of the congruity between these would be valuable (the mean basal ADRR of adrenal adenoma patients was ca.…”
Section: Discussionmentioning
confidence: 67%
“…In these studies, the diagnosis of PA was based on the standard methodology initially using as a screening test the basal PAC/PRA ratio and as confirmatory test mainly the 2 lt saline infusion. This choice significantly reduces the sensitivity of these diagnostic tests because they aim to suppress only the renin-angiotensin II-system, leaving the secretion of ACTH unaffected [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…To define the normal response of ALD and ARR to the ultra-low ACTH test, 23 normotensive individuals with normal adrenals examined by CT or magnetic resonance imaging (MRI) were recruited and served as controls. Normotensive PA was excluded using the D-SIT (dexamethasone-saline infusion test) diagnostic method [ 17 ]. We preferred the use of D-SIT instead of FDST because it was easier to use and, therefore, better acceptable by the NC group.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that biochemically overt PA is not a rare entity in patients with adrenal incidentaloma and normal blood pressure. [77,78] Kmieć and colleagues conducted a prospective study attempting to detect subclinical autonomous aldosterone secretion in patients with adrenal incidentaloma by using permissive criteria of ARR >1.2 (ng/dL)/(mIU/L) (approximately 10 (ng/dL)/(ng/mL/hour)) and plasma aldosterone concentration >4 ng/dL. Normotensive patients with urine aldosterone excretion >10 µg/day were considered to have mild autonomous aldosterone secretion, while hypertensive patients with urine aldosterone >12 µg/day were diagnosed with overt PA.…”
Section: Reported Prevalence Of Overt Pa In Patients With Adrenal Inc...mentioning
confidence: 99%
“…An unresolved question regarding the evaluation of adrenal incidentaloma is whether we should screen for autonomous aldosterone production in patients who do not have hypertension. It has been suggested that biochemically overt PA is not rare in patients with adrenal incidentaloma and normal blood pressure [77,78]. Kmieć and colleagues conducted a prospective study attempting to detect subclinical autonomous aldosterone secretion in patients with adrenal incidentaloma by using permissive criteria of ARR > 1.2 (ng/dL)/(mIU/L) (approximately 10 (ng/dL)/(ng/mL/h)) and plasma aldosterone concentration > 4 ng/dL.…”
Section: The Reported Prevalence Of Overt Primary Aldosteronism In Pa...mentioning
confidence: 99%